Perbandingan Pengaruh Latihan Ladder In Out Dengan 40-yard Lateral Shuffel Terhadap Peningkatan Kelincahan - Rahmawan, Dani; Risma, Risma; Nursasih, Isna Daniyati (Jurnal Keolahragaan, 2023)
This study aims to determine the increase in agility. The research method uses a pre-experimental design. The population used was the male students of MTs Negeri 1 Pangandaran who took part in volleyball extracurricular activities, totaling 30 people. The sampling technique used was the total sampling technique. The test instrument or measuring tool used is the shuttle run test. Based on data analysis using SPSS series 24, the results of data processing consist of 1. Ladder-in-out exercises have a significant effect on increasing body agility in students of MTs Negeri Pangandaran. The 40-yard lateral shuffle exercise has a significant effect on increasing body agility in MTs Negeri Pangandaran students. 3. There is no significant difference in the effect of the ladder in out exercise and the 40-yard lateral shuffle exercise on increasing body agility in students of MTs Negeri Pangandaran. Conclusion: Ladder in-out exercise with 40-yard lateral shuffel exercise to increase body agility in students of MTs Negeri Pangandaran.